(untitled) (Bangladesh Journal of Medical Science, 2018)
Objectives: In order to deal with professional ethical issues successfully, nurses and other providers of clinical care need to rely on professional values that are meant to guide their professional decision-making, actions and behaviors .These values form the basis of nursing. Accordingly, the present study aims to investigate nurses’ perception of professional values in the hospitals affiliated with Jahrom University of Medical Sciences. Method: In this descriptiveanalytical study, 100 nurses employed at the university hospitals of Jahrom were selected through simple convenience sampling. To examine the subjects’ perception of professional values, the researchers used a two-part questionnaire: part one consisted of questions about the personal and social characteristics of the subjects; part two was the Nurses Professional Values Scale-Revised. The latter consists of 26 items based on American Nurses Association Code of Ethics for Nurses and addresses the following areas: caring (9 items), activism (5 items), trust (5 items), professionalism (4 items) and justice (3 items).Answers are scored based on a 5-point Likert scale: the answer choices “Not important” and “Very important” are assigned 1 point and 5 points respectively. The score range is between 26 and 130—higher scores indicate the respondent’s greater familiarity with professional values. Findings: The participants of the study consisted of 99 nurses who were selected from the various parts of the university hospitals of Jahrom. The participants’ mean scores for caring, activism, trust, professionalism, justice and total perception of professional values were found to be 32.15,15.47, 17.37, 13.32,10.66 and 88.98 respectively. The results of the study showed that there was not a significant relationship between the age, gender and marital status of nurses on one hand and their professional values scores on the other (P=0.7). Conclusion: There is need for effective programs to enhance nurses’ awareness of certain of their professional duties and improve their professional performance in a wide range of professional areas alongside their duties as care-givers. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.47-51